1988
DOI: 10.1073/pnas.85.5.1339
|View full text |Cite
|
Sign up to set email alerts
|

Tris(tetramethylphenanthroline)ruthenium(II): a chiral probe that cleaves A-DNA conformations.

Abstract: A-Tris (3,4,7,8-tetramethyl-1,10-phenanthroline)ruthenium(ll) [A-Ru(TMP)2+] was found to be a distinctive molecular tool to examine the local variations in conformation along the strand. The metal complex binds cooperatively to A-form helices of various base sequences under conditions where little or no binding was found to analogous B-form DNAs. Photoactivated DNA cleavage may be coupled to this conformation-specific binding by taking advantage of the photophysical properties of ruthenium(ll) complexes. ARu(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(69 citation statements)
references
References 39 publications
5
64
0
Order By: Relevance
“…It is important to understand the mode of action of anticancer drugs to improve their design and their use in combinatory or tumor-selective treatments. Numerous studies indicated that ruthenium-derived compounds interact with DNA (20)(21)(22), which is consistent with our previous finding that RDCs induce p53 (23). RDC11 can also induce p53 protein levels (Fig.…”
Section: Rdc11 Inhibits the Growth Of Various Tumors Implanted In Micesupporting
confidence: 81%
See 1 more Smart Citation
“…It is important to understand the mode of action of anticancer drugs to improve their design and their use in combinatory or tumor-selective treatments. Numerous studies indicated that ruthenium-derived compounds interact with DNA (20)(21)(22), which is consistent with our previous finding that RDCs induce p53 (23). RDC11 can also induce p53 protein levels (Fig.…”
Section: Rdc11 Inhibits the Growth Of Various Tumors Implanted In Micesupporting
confidence: 81%
“…Based on the similarities with platinum compounds (19), studies on the mode of action of ruthenium-containing compounds focused on their interaction with DNA (20)(21)(22). Indeed, several ruthenium-containing drugs interact with DNA and modify its structure, suggesting that they might induce DNA damages.…”
Section: Introductionmentioning
confidence: 99%
“…But normal lung cells of MRC-5 were only slightly affected by the interaction of the Ru(II) complex with DNA in contrast to A549 tumor cells in the presence of the Ru(II) complex. It has been reported that the quercetin zinc(II) complex [39], hedamycin [40], and tris(tetramethylphenanthroline) Ru(II) [41] intercalate into the GC-rich core promoter region of survivin, down-regulating surviving gene expression and promoting tumor cells apoptosis. Therefore, we deduced that the Ru(II) complex intercalated into DNA and thereby induced apoptosis in tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is of interest to note that [Ru(phen) 3 ]Cl 2 has been reported to involve a singletoxygen ( 1 O 2 )-mediated DNA-photocleavage mechanism [42]. To identify the nature of the reactive species responsible for photo-activated cleavage of plasmid DNA, we further investigated the influence of different potentially inhibiting agents.…”
Section: 5mentioning
confidence: 99%